A comparative profile of intimate partner sexual violence - Jung, Sandy; Faitakis, Martina; Cheema, Harleen (My University, 2021)
Sexual violence is prevalent in abusive relationships and yet, has received substantially less attention than physical violence in relationships or sexual violence, in general. The present study compared intimate partner sexual violence (IPSV) with non-sexual intimate partner violence (IPV) and sexual violence against other non-intimate partner victims on demographic data of perpetrators and victims, offence and police reporting features, and the perpetrators’ criminal history and recidivism. Sexual and violent assaults reported to local law enforcement that led to an arrest were randomly selected. Analyses revealed that IPSV occurrences took longer to report compared to the other violent occurrences. However, IPSV was similar to IPV occurrences in that weapons were rarely involved, occurrences were more likely outside of the downtown area, and perpetrators were younger. These findings contribute to our limited knowledge about IPSV perpetration and highlight avenues for future exploration in the literature.
Keywords: intimate partner violence; sexual violence; police-reported; spousal assault; intimate partner sexual violence